2010
DOI: 10.1080/17441690802551340
|View full text |Cite
|
Sign up to set email alerts
|

Understanding women's experiences with medical abortion: In-depth interviews with women in two Indian clinics

Abstract: We explored women's perspectives on using medical abortion, including their reasons for selecting the method, their experiences with it and their thoughts regarding demedicalisation of part or all of the process. Sixty-three women from two urban clinics in India were interviewed within four weeks of abortion completion using a semi-structured in-depth interview guide. While women appreciated the non-invasiveness of medical abortion, other factors influencing method selection were family support and distance fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 4 publications
1
38
0
Order By: Relevance
“…In legal settings, we found that the older studies described more medicalized approaches that required women to remain in clinic for four hours following misoprostol administration. 16,17 Shifts to less medicalized care in the more recent studies took the following forms: administering the misoprostol to women at the second appointment but then sending them home to abort, [18][19][20]4 giving women misoprostol at the second appointment but allowing them to selfadminister it at home, 18,21 giving women misoprostol at the first appointment to be self-administered at home, 19,[22][23][24][25][26][27] and giving women both mifepristone and misoprostol at the first appointment to be taken at home. 27,28 The studies from legal settings that reported misoprostol-only abortions reported self-administration at home.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In legal settings, we found that the older studies described more medicalized approaches that required women to remain in clinic for four hours following misoprostol administration. 16,17 Shifts to less medicalized care in the more recent studies took the following forms: administering the misoprostol to women at the second appointment but then sending them home to abort, [18][19][20]4 giving women misoprostol at the second appointment but allowing them to selfadminister it at home, 18,21 giving women misoprostol at the first appointment to be self-administered at home, 19,[22][23][24][25][26][27] and giving women both mifepristone and misoprostol at the first appointment to be taken at home. 27,28 The studies from legal settings that reported misoprostol-only abortions reported self-administration at home.…”
Section: Resultsmentioning
confidence: 99%
“…They often reported some degree of anxiety at the beginning of the process but reported relief at the end and a strong sense of satisfaction with the choice to self-manage. 19,20,22,23,29 In some contexts, the use of misoprostol at home for early medical abortion falls within existing interpretive frameworks and practices (such as "menstrual regulation" (Bangladesh) and was understood as one of many treatments for local illness categories referring to missed menstrual periods (e.g. "late menses" in Brazil).…”
Section: General Perceptions Of Self-management Of Medical Abortionmentioning
confidence: 99%
See 3 more Smart Citations